(a) 2x + 5x + 4 = 25 <== ur equation
7x + 4 = 25
7x = 25 - 4
7x = 21
x = 21/7
x = 3
(b) first piece = 2x....= 2(3) = 6 ft <=
second piece = 5x....= 5(3) = 15 ft <=
━━━━━━━☆☆━━━━━━━
▹ Answer
<em>60 1/8 or 481/8</em>
<em> </em>
▹ Step-by-Step Explanation
![6 \frac{1}{2} * 9 \frac{1}{4} \\\\= \frac{13}{2} * \frac{37}{4} \\\\= \frac{481}{8} \\\\= 60\frac{1}{8} or \frac{481}{8}](https://tex.z-dn.net/?f=6%20%5Cfrac%7B1%7D%7B2%7D%20%2A%209%20%5Cfrac%7B1%7D%7B4%7D%20%5C%5C%5C%5C%3D%20%5Cfrac%7B13%7D%7B2%7D%20%2A%20%5Cfrac%7B37%7D%7B4%7D%20%5C%5C%5C%5C%3D%20%5Cfrac%7B481%7D%7B8%7D%20%5C%5C%5C%5C%3D%2060%5Cfrac%7B1%7D%7B8%7D%20or%20%5Cfrac%7B481%7D%7B8%7D)
Hope this helps!
- CloutAnswers ❁
Brainliest is greatly appreciated!
━━━━━━━☆☆━━━━━━━
Answer:
C. two thirds x + 10 = 21
Step-by-step explanation:
Given
Price of adult ticket = $21.00
Let x be the price of student ticket
Then
two third of the student ticket will be:
![\frac{2}{3} x](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D%20x)
The statement $10.00 more than two third of student ticket:
![\frac{2}{3} x+10](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D%20x%2B10)
As we are given in the question that the adult ticket price is $21.00 and the second explanation is th equation formed by the given statement
So, both will be equivalent
![\frac{2}{3} x+10 = 21](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D%20x%2B10%20%3D%2021)
Solving this equation for x will give us the price for the student ticket.
Hence,
C. two thirdsx + 10 = 21 is the correct answer ..
Answer:
The approximate probability that more than 360 of these people will be against increasing taxes is P(Z> <u>0.6-0.45)</u>
√0.45*0.55/600
The right answer is B.
Step-by-step explanation:
According to the given data we have the following:
sample size, h=600
probability against increase tax p=0.45
The probability that in a sample of 600 people, more that 360 people will be against increasing taxes.
We find that P(P>360/600)=P(P>0.6)
The sample proposition of p is approximately normally distributed mith mean p=0.45
standard deviation σ=√P(1-P)/n=√0.45(1-0.45)/600
If x≅N(u,σ∧∧-2), then z=(x-u)/σ≅N(0,1)
Now, P(P>0.6)=P(<u>P-P</u> > <u>0.6-0.45)</u>
σ √0.45*0.55/600
=P(Z> <u>0.6-0.45)</u>
√0.45*0.55/600
Answer:
20
Step-by-step explanation:
Divide 62.8 by 3.14